Exploring the link between poor oral hygiene and mesh infection after hernia repair: a systematic review and proposed best practices - East, B; Podda, M; Beznosková-Seydlová, M; de Beaux, A C (Hernia, 2023)
BACKGROUND: There is a reasonable body of evidence around oral/dental health and implant infection in orthopaedic and cardiovascular surgery. Another large area of surgical practice associated with a permanent implant is mesh hernia repair. This study aimed to review the evidence around oral/dental health and mesh infection. METHODS: The research protocol was registered in PROSPERO (CRD42022334530). A systematic review of the literature was undertaken according to the PRISMA 2020 statement. The initial search identified 582 publications. A further four papers were identified from references. After a review by title and abstract, 40 papers were read in full text. Fourteen publications were included in the final review, and a total of 47,486 patients were included. RESULTS: There is no published evidence investigating the state of oral hygiene/health and the risk of mesh infection or other infections in hernia surgery. Improvement in oral hygiene/health can reduce surgical site infection and implant infection in colorectal, gastric, liver, orthopaedic and cardiovascular surgery. Poor oral hygiene/health is associated with a large increase in oral bacteria and bacteraemia in everyday activities such as when chewing or brushing teeth. Antibiotic prophylaxis does not appear to be necessary before invasive dental care in patients with an implant. CONCLUSION: Good oral hygiene and oral health is a strong public health message. The effect of poor oral hygiene on mesh infection and other complications of mesh hernia repair is unknown. While research is clearly needed in this area, extrapolating from evidence in other areas of surgery where implants are used, good oral hygiene/health should be encouraged amongst hernia patients both prior to and after their surgery.
Keywords: inguinální hernie; operace kýly; Oral Hygiene; lidé; chirurgické síťky; infekce chirurgické rány; Humans; Surgical Wound Infection; Hernia, Inguinal; Surgical Mesh; orální hygiena; Herniorrhaphy